Peran Komunikasi Profetik Dalam Pembentukan Etika Santri Di TPA Percontohan Anwar Rasyid Provinsi DIY - Rahman, Taufik - (Hikmah, 2025)
Prophetic communication, inspired by the example of Prophet Muhammad SAW, represents a multidimensional form of interaction that transcends eras and generations. It integrates moral, spiritual, and humanistic values within the process of conveying messages. This research explores the role of prophetic communication as practiced by the leader of TPA Anwar Rasyid, Yogyakarta, in shaping the ethics of students. Using a qualitative approach, data were collected through in-depth interviews with the TPA director and direct observation of teaching and learning activities. The study focuses on how communication methods inspired by prophetic values influence students’ moral development and behavior both within and beyond the learning environment. The findings reveal that the director of TPA Anwar Rasyid consistently applies prophetic communication principles such as honesty, empathy, compassion, and patience, reflecting the communication ethics exemplified by the Prophet Muhammad SAW. This communication model emphasizes dialogical engagement, mutual respect, and moral instruction through personal example rather than verbal persuasion alone. Consequently, the learning environment at TPA Anwar Rasyid fosters students who are respectful, disciplined, and spiritually aware. The integration of prophetic communication within educational activities not only enhances academic outcomes but also strengthens students’ character and interpersonal ethics. Therefore, this study concludes that prophetic communication plays a crucial role in shaping ethical behavior, contributing to the success of TPA Anwar Rasyid as a model institution for Islamic moral education